Prognostic Value of Immunohistochemical Staining of p53, bcl-2, and Ki-67 in Small Cell Lung Cancer - Paik, Kwang Hyun (The Korean Academy of Medical Sciences, 2006)
Small cell lung cancer (SCLC) is one of the most fatal cancers in humans and many factors are known to be related to its poor prognosis. Immunohistochemical (IHC) stainings were done on SCLC specimens in order to investigate the prognostic value of the apoptosis-related gene expression and the tumor proliferative maker, and the relationships among these IHC results and patients clinical characteristics, chemoresponsiveness, and survival were analyzed. The medical records of 107 patients were reviewed retrospectively. IHC stainings for p53, bcl-2 and Ki-67 expressions were performed in the 66 paraffin-embedded biopsy samples. Sixty-six out of the 107 patients were evaluable for response rate and survival. The overall response rate was 75% (95% Confidence Interval=74-76%) and the median survival time was 14 months. The median survival time of limited stage was 16 months and that of extensive stage was 10 months. The prevalence of p53, bcl-2 and Ki-67 expression was 62%, 70%, and 49%, respectively. There were no correlations among the immunoreactivities of p53, bcl-2 and Ki-67 with clinical stage, chemoresponsiveness or overall survival. The clinical stage was the only prognostic factor influencing survival. The expression rates of p53, bcl-2, and Ki-67 were relatively high in SCLC without any prognostic significance. The exact clinical role of these markers should be defined through further investigations.